Strategi Kebijakan Pemerintah dalam Menanggulangi Trauma Sosial Pasca-Konflik di Ambon - Muslem Muslem (Kajian Administrasi Publik dan ilmu Komunikasi, 2024)
This study examines the impact of government policies on social trauma healing and post-conflict social integration in Ambon, focusing on interfaith community relations and policies implemented following the Malino II Agreement. The objective of this research is to explore the effectiveness of reconciliation policies in reducing sectarian tensions and supporting the recovery of social trauma. The study employs a descriptive-analytical qualitative approach, utilizing a literature review of relevant sources, including books and articles on related policies. The findings indicate that reconciliation policies involving interfaith dialogue and engagement with local leaders have been effective in mitigating sectarian tensions and fostering social trauma recovery. However, while these policies have shown short-term effectiveness, challenges persist in ensuring their sustainability and implementation, particularly regarding social inclusivity. Additionally, the role of local religious leaders and religious institutions is crucial in creating spaces for dialogue and strengthening social cohesion, while religious education and local cultural practices also contribute to social integration. This study suggests that community-based approaches and inclusive policies that engage various societal elements are essential for achieving sustainable social peace.